Hubungan Dukungan Keluarga Terhadap Motivasi Pasien Kanker Payudara Dalam Menjalani Kemoterapi Di Ruang Cendrawasih I Rsud Arifin Achmad Provinsi Riau - Mahwita Sari; Yulia Irvani Dewi; Agnita Utami (Fakultas Keperawatan, Universitas Riau, 2012)
This study aims to determine the corelation between family’s support to motivation of breast cancer patients in undergoingchemotherapy at Cendrawasih I Arifin Achmad Hospital in Riau Province. The research used quantitative with descriptivecorrelation design, and used crosssectional approach. Total sample in this research was 37 respondents with ConsecutiveSampling technique. Measurement tools that has been used a questionnaire. Data was analyzed by using univariate andbivariate analysis with chi – square tests. The results obtained p value =0.008 (pvalue <0,05) with OR=9,000 (95% CI = 1,958-41,364). So it can be conclude there are significant corelation between family’s support to motivation of breast cancer patientsin undergoing chemotherapy. Based on the result, it will suggested for Arifin Achmad Hospital Riau Province to be abledevelopment health services in community for improving the quality of service, especially in motivating breast cancer patientundergoing chemotherapy and establish programme associations of patient and their family.Keyword: Family support, motivation, breast cancer.